2002
DOI: 10.1007/s00705-001-0794-y
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenicity and vaccine efficacy of a thymidine kinase gene deleted infectious laryngotracheitis virus expressing the green fluorescent protein gene

Abstract: The deletion of the thymidine kinase (TK) gene of herpesviruses causes a reduction in their virulence. However, the effects of the TK gene in infectious laryngotracheitis virus (ILTV) have not been clearly elucidated. In the present study, we constructed a TK gene-deleted recombinant ILTV expressing the green fluorescent protein (GFP) gene as a marker. The GFP gene was inserted in place of the TK gene in both virulent and low virulence strains of ILTV. The GFP gene in the recombinants was expressed in chicken … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…Some viruses with deleted genes may retain their ability to induce immune response while not producing clinical signs or latency. ILT viruses with deletions of the genes gC (Pavlova et al, 2010), gG (Devlin et al, 2006), gJ (Fuchs et al, 2005), TK (Han et al, 2002), UL0 (Veits et al, 2003), and UL 47 (Helferich et al, 2007) showed attenuation and may be used for vaccine production. A gG-deficient ILTV strain administered to 3-week-old SPF chickens via drinking water and eye drop induced adequate immunity against challenge with a wild strain and may potentially be used for large-scale vaccination; however, further studies are needed before it is applied to commercial poultry flocks (Devlin et al, 2008).…”
Section: Epidemiology Of Avian Infectious Laryngotracheitis With Specmentioning
confidence: 99%
“…Some viruses with deleted genes may retain their ability to induce immune response while not producing clinical signs or latency. ILT viruses with deletions of the genes gC (Pavlova et al, 2010), gG (Devlin et al, 2006), gJ (Fuchs et al, 2005), TK (Han et al, 2002), UL0 (Veits et al, 2003), and UL 47 (Helferich et al, 2007) showed attenuation and may be used for vaccine production. A gG-deficient ILTV strain administered to 3-week-old SPF chickens via drinking water and eye drop induced adequate immunity against challenge with a wild strain and may potentially be used for large-scale vaccination; however, further studies are needed before it is applied to commercial poultry flocks (Devlin et al, 2008).…”
Section: Epidemiology Of Avian Infectious Laryngotracheitis With Specmentioning
confidence: 99%
“…Among the 20 gene-deleted ILTV strains generated, only seven have been evaluated in vivo for attenuation and protection efficacy. Individually, these mutants contained deletions in the genes encoding a nuclear protein of unknown function (U L 0 gene), (Veits et al, 2003b), thymidine kinase (U L 23) (Han et al, 2002;Schnitzlein et al, 1995), dUTPase (U L 50) (Fuchs et al, 2000), glycoprotein G (U S 4) (Devlin et al, 2006), glycoprotein J (U S 5) Mundt et al, 2011), glycoprotein C (U L 44) (Pavlova et al, 2010), and the tegument protein (U L 47) (Helferich et al, 2007). Growth kinetics analysis of these gene deletion recombinants indicated that they are non-essential for virus replication in cell culture (Fuchs et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Growth kinetics analysis of these gene deletion recombinants indicated that they are non-essential for virus replication in cell culture (Fuchs et al, 2007). In chickens the DU L 50 (dUTPase) (Fuchs et al, 2000) and DU L 44 (gC) (Pavlova et al, 2010) gene-deleted recombinants still exhibited some degree of virulence, while the DU S 4 (gG) (Devlin et al, 2006), DU L 47 (tegument protein) (Helferich et al, 2007), DU L 23 (thymidine kinase) (Han et al, 2002), DU L 0 (nuclear protein) (Veits et al, 2003b), and DU S 5 (gJ) recombinants exhibited moderate to marked degrees of attenuation.…”
Section: Introductionmentioning
confidence: 99%
“…Although only four out of the 73 ILTVpredicted open reading frames (Thureen & Keeler, 2006) were utilized to separate viral genotypes, this analysis provided the framework to compare the pathogenicity and growth characteristics of different ILTV genotypes. The pathogenicity of ILTV isolates has been evaluated measuring the trachea microscopic pathology induced by different ILTV isolates after intra-tracheal inoculation (Guy et al, 1990;Han et al, 2002). Most recently the pathogenicity of vaccines and field strains was evaluated considering clinical signs, body weight gain, and the presence of viral DNA in the trachea .…”
Section: Introductionmentioning
confidence: 99%